Corrosion inhibition of copper in sodium chloride solution using polyetherimide/graphene composites. (28th March 2016) - Alhumade, Hesham; Abdala, Ahmed; Yu, Aiping; Elkamel, Ali; Simon, Leonardo
Abstract: In this study, polyetherimide‐graphene composites (PEI/G) were prepared and investigated as corrosion inhibition coatings on copper substrates. Various loadings of graphene were incorporated in the polyetherimide matrix using an in situ polymerization approach, and the composite coatings were cured by thermal imidization. The effect of graphene loading on corrosion inhibition and the long‐term performance of the PEI/G coatings were investigated. The dispersion of graphene in the polymer matrix was examined using SEM and TEM. The study demonstrated that PEI/G nanocomposites provide advanced corrosion inhibition of copper. This conclusion was supported by the results of various electrochemical techniques such as Tafel polarization and electrochemical impedance spectroscopy (EIS). In addition to corrosion protection, the long‐term performance of the coatings was confirmed by testing the adhesion of PEI/G composites to copper substrates before conducting the electrochemical tests and after 15 days of exposure to the corrosive medium.